STUDI LITERATUR: SEMIOTIK SEBAGAI ILMU YANG MEMPELAJARI TANDA-TANDA DALAM KARYA SASTRA - Panuluh, Aditio Damar; Puspita, Dede; Jaenalludin, Jaenalludin; Fidiyah, Tasyah; Julianto, Indra Rasyid (Jurnal Pesastra (Pendidikan Bahasa dan Sastra), 2025)
Semiotics is a branch of literary sciences that focuses on the study of signs. In literary works, poets often use signs and signifiers to enhance the beauty of their creations, making them more enjoyable for readers and listeners. However, the meanings and messages conveyed in these works can sometimes be difficult to understand, leaving the audience confused. Semiotics, as a discipline, helps simplify the process of interpreting a literary work, though it serves as only a foundational tool for understanding literature. Semiotics itself is the science that examines the signs within literary works, ensuring that readers and listeners grasp the true message intended by the poet. Studying these signs through semiotic analysis involves various methods, such as the descriptive method, which presents the objects and subjects under study as they are; the qualitative method, which is closely related to the descriptive method and involves collecting, organizing, and analyzing qualitative data; and the literature study method, which requires gathering relevant data or documents for research purposes. In conclusion, to fully comprehend the signs and derive the true meaning of a literary work through semiotic analysis, one must first understand these three methods, as explained by experts in the field.